EXOGENOUS APPLICATION OF NAPHTHALENE ACETIC ACID IMPROVES FRUIT SIZE AND QUALITY OF KINNOW MANDARIN (Citrus reticulata) T HROUGH REGULATING FRUIT LOAD - F. Shireen; M. J. Jaskani; M. A. Nawaz; F. Hayat (Journal of Animal and Plant Sciences, 2018)
Citrus fruits are produced across the world because of their adaptability to different climatic conditions. Present study -1 -1 -1 -1 was executed to investigate the effect of naphthalene acetic acid ( NAA) ( 0 mg.l , 200 mg.l , 300 mg.l , 400 mg.l , 500 -1 mg.l ) on fruit thinning, fruit development ( fruit size, weight), and physio-chemical attributes [juice percentage, total soluble solids (TSS), titrateable acidity ( TA), ascorbic acid, total sugars, reducing sugars, and non-reducing sugars] of seedless Kinnow mandarin. This study was conducted on ten years old Kinnow (Citrus reticulata Blanco) plants grafted onto Rough lemon ( Citrus jambhiri Lush.) . Experiment was laid out according to randomized complete block design with three replicates per treatment. Foliar application of NAA was done on experimental plants after the June drop. NAA -1 -1 at 500 mg.l caused heavy fruit thinning by reducing the crop load up to 55% whereas, 200 mg.l NAA reduced the crop -1 load up to 13%. As for as the fruit quality is concerned; NAA at the concentration of 200 mg.l enhanced per fruit -1 weight, juice percentage, and TSS compared with control. In conclusion, foliar application of NAA (200 mg.l ) after the June drop can be utilized as thinning agent for Kinnow mandarin to improve the fruit size and other fruit quality attributes. breakage due to heavy crop load, collectively lead
Keywords: Citrus reticulata; Fruit load; Fruit quality; Fruit thinning; NAA.